Impact of contract farming on householders' income, intensification, and land productivity in Ethiopia: evidence from smallholder malt barley producers in the highlands of the Central and Southern Oromia region - Tamrat Gebiso Challa; Ephrem Boka Dube; Ibsa Dawid; Eihab Fathelrahman (Frontiers in Environmental Economics)
IntroductionContract farming (CF) is an agreement between farmers and processing and/or marketing firms for the production and supply of agricultural products under forward agreements, frequently at predetermined prices. Malt barley–producing smallholder farmers in Ethiopia are engaged in CF with different malt factories and breweries in the Arsi and West Arsi zones. However, factors affecting participation in CF and its impact on households' welfare and input use have not been well studied so far.MethodsWe address this gap by first describing the CF models practiced in the study area. Subsequently, we identify the factors that induce farmers to participate in CF and estimate the impact of participation in CF on households' income, intensification, and land productivity. For that purpose, the barley-producing households were clustered as participants and non-participants in CF. Household-level data from 248 randomly sampled households were collected by face-to-face interviews using a structured questionnaire. In addition, focus group discussions (FGDs), key informant interviews (KIIs), and secondary data were used to substantiate the household-level data. Finally, narrative summaries and propensity score matching were used for data analysis and interpretation.Results and discussionThe FGD and KII results showed that smallholders tend to participate in intermediary and resource-providing CF types. Malt barley producers' participation in these CF schemes proved to be positively correlated with education level, land size allocated to malt barley, participation in crop output marketing, and household income. The average treatment effect on treated results showed that CF participant households generated US$744.63 1 more than non-participants. Malt barley CF participation also led to increased fertilizer application per household, resulting in increased malt barley production. The results confirm that CF participation can raise yields as well as household income thanks also to better direct connections between producers and agribusinesses (such as breweries and malt mills). It is therefore essential for policymakers and practitioners to support these linkages and establish additional platforms for interaction.